Interlinkage among cardio-metabolic disease markers in an urban poor setting in Nairobi, Kenya - Tilahun Nigatu Haregu; Samuel Oti; Nicholas Ngomi; Christopher Khayeka-wandabwa; Thaddaeus Egondi; Catherine Kyobutungi (Taylor & Francis Group, 2016)
Introduction: The main cardio-metabolic diseases - mostly cardiovascular diseases such as stroke and ischemic heart disease - share common clinical markers such as raised blood pressure and blood glucose. The pathways of development of many of these conditions are also interlinked. In this regard, a higher level of co-occurrence of the main cardio-metabolic disease markers is expected. Evidence about the patterns of occurrence of cardio-metabolic markers and their interlinkage in the sub-Saharan African setting is inadequate. Objective: The goal of the study was to describe the interlinkage among common cardio-metabolic disease markers in an African setting. Design: We used data collected in a cross-sectional study from 5,190 study participants as part of cardiovascular disease risk assessment in the urban slums of Nairobi, Kenya. Five commonly used clinical markers of cardio-metabolic conditions were considered in this analysis. These markers were waist circumference, blood pressure, random blood glucose, total blood cholesterol, and triglyceride levels. Patterns of these markers were described using means, standard deviations, and proportions. The associations between the markers were determined using odds ratios. Results: The weighted prevalence of central obesity, hypertension, hyperglycemia, hypercholesterolemia, and hypertriglyceridemia were 12.3%, 7.0%, 2.5%, 10.3%, and 17.3%, respectively. Women had a higher prevalence of central obesity and hypercholesterolemia as compared to men. Blood glucose was strongly associated with central obesity, blood pressure, and triglyceride levels, whereas the association between blood glucose and total blood cholesterol was not statistically significant. Conclusions: This study shows that most of the common cardio-metabolic markers are interlinked, suggesting a higher probability of comorbidity due to cardio-metabolic conditions and thus the need for integrated approaches.